METHODOLOGY FOR DEVELOPING STUDENTS' TECHNICAL CREATIVITY BASED ON THE STEM APPROACH (USING THE EXAMPLE OF TEACHING PHYSICS) (Web of Teachers: Inderscience Research, 2024)
Increasing the creative abilities of students is one of the modern demands of the educational system. This article discusses the methodology of increasing creative abilities in physics classes through STEM-educational technology.